Determination of Fatty Acid Content in Six Common Marine Fishes in Bangladesh - Khatun, Marzia; Mostafa, Md. Golam; Anwarul Hasan, G. M. M.; Morshed, Mahbubul (British Journal of Healthcare and Medical Research, 2023)
A comparative study on the fatty acid contents of six common marine fishes: Poa (Poa poa), Rupchanda (Chinese pomfret), Hilsha (Tenualosa ilisha), Loita (Harpadon nehereus), Baila (Hemibagrus menoda) and Chapila (Gudusia chapra) were carried out by Gas Chromatography-Tandem Mass Spectrometry (GC-MS/MS). Saturated and unsaturated fatty acids, notably monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) were shown to be more advantageous; these fatty acids are found in marine fishes. The polyunsaturated fatty acids Eicotetraenoic acid (C20:4), 12Z, and 15Z-heneicosadienoic acid (C21:2) are found in Rupchanda fish. Hilsha fish contained the monounsaturated fatty acids- Palmitoleic acid (C16:1) and Oleic acid (C18:1), which are respectively omega-7 and omega-9. Chapila fish contained the monounsaturated fatty acids such as cis-10 pentadecanoic acid (C15:1) and cis-15-tetracosenoic acid (C24:1). Only one mono unsaturated fatty acid, pentadecanoic acid (cis-10) (C15:1) is found in Loita fish species. However, the six selected marine fishes also showed several saturated fatty acids. Pentadecanoic acid (C15:0) was the most common saturated fatty acid identified in all studied marine fishes. However, this study suggests that, fatty acid profiles and concentration of the marine fishes will evaluate the fatty acids contents of that fishes to appraise the health benefits.